The ethics of psycho analysis 1959-1960 - Lacan, Jacques (Routledge, 2012)
A charismatic and controversial figure, Lacan is one of the most important thinkers of the twentieth century and his work has revolutionized linguistics, philosophy, literature, psychology, cultural and media studies.